Selenium Decorated Reduced Graphene Oxide Supported CoSe2 Nanoparticles as Efficient Electrochemical Catalyst for the Oxygen Reduction Reaction. Issue 21 (3rd September 2018) - Zhao, Yuan; Zhang, Chuanxiang; Fan, Rong; Li, Jingxiu; Hao, Yanan; He, Jianping; Alonso‐Vante, Nicolas; Xue, Jianjun
Abstract: Developing efficient electrocatalysts for the oxygen reduction reaction (ORR) based on non‐precious catalytic centers is critical to improve the efficiency of low temperature fuel cells. Herein, we report on a catalyst containing CoSe2 supported on selenium decorated reduced graphene oxide (CoSe2 /Se‐rGO), which was synthesized via a one‐pot solvothermal method using Se‐rGO as support. Importantly, the CoSe2 /Se‐rGO showed an enhanced catalytic activity for ORR in alkaline medium with an onset potential of 0.903 V vs. RHE and a half‐wave potential of 0.803 V vs. RHE. Its stability and methanol tolerance ability were significantly improved as compared to 20 wt% Pt/C, respectively. The strategy developed here provided a novel and efficient approach to prepare non‐precious electrocatalysts for ORR. Abstract : Uniform dispersion : Selenium decorated reduced graphene oxide supported cobalt selenide CoSe2 /Se‐rGO is synthesized by a one‐pot solvothermal route. Selenium on the surface of rGO acts as a nucleation site, inducing the uniform dispersion of CoSe2 on the surface of graphene. The electrocatalytic performance for oxygen reduction reaction (ORR) in alkaline medium is enhanced.